Respuestas

2013-02-16T12:59:00+01:00

A = x3(m + 9) ^x5 (m + 1) / x13 ( m + 1) = x3 (m + 9) ^x5 / x13 = x8^(m + 9) / x13 = (m+9) / x5

  • Usuario de Brainly
2013-02-16T18:38:21+01:00

Yo lo entiendo de la sgte. manera :

A = [x^(3) * (m+9 )]*[x^(5)*(m-1)]/ x^(13)*(m-1)

Simplificamos "(m-1)" :

A = [x^(3) *(m+9) * x^(5)]/x^(13)

Propiedad de las potencias " Mismas bases , se suman los exponenes" :

A = [ x^(5+3)*(m+9)]/x^(13)

  A = [ x^(13)*(m+9)]/x^(13)

Simplificamos "x^(13)" :

A = (m+9)   ---> Rpta.

   SaLuDos :)'